Reflexões sobre gênero e sexualidade no ambiente educacional em uma escola família agrícola no noroeste do Espírito Santo - Pereira, Patrick (2023)
This study investigates the integration of gender and sexuality issues in a Family Agricultural School in the Northwest of Espírito Santo, taking into account its specific characteristics. This research is part of a broader study, stemming from the need to address the topics of sexual orientation, gender, and sexuality in rural education and Alternative Pedagogy. The central research question was: How can educational strategies promote an understanding of gender and sexuality in the Family Agricultural School, considering its uniqueness and the evolving perspectives of educators and students? The general objective was to analyze the approach to gender and sexuality in the Family Agricultural School in the Northwest of Espírito Santo. The specific objectives aimed to investigate the perceptions and attitudes of educators, assess the perspectives of students, and explore cultural influences. The theoretical framework is based on various academic sources, with an emphasis on the contribution of Lopes (2003, 2004, 2009, 2019), renowned for their critical analysis of gender and sexuality issues in the educational context. A qualitative approach was adopted, combining literature review, case study, and interviews, which allowed for an examination of the complexity of gender and sexuality issues in the school. The interviews revealed that the school can be a source of prejudice, with students and teachers contributing to homophobic practices. The results underscore the need for training for the educators and the urgency of addressing these issues in a more inclusive and context-sensitive manner. A genuine desire on the part of educators and students to improve understanding and the educational environment regarding gender and sexuality is identified, with the aim of moving towards a more inclusive and equitable education in these schools and similar contexts.